Characterisation of a nucleo-adhesome - Byron, Adam; Griffith, Billie G. C.; Herrero, Ana; Loftus, Alexander E. P.; Koeleman, Emma; Kogerman, Linda; Dawson, John C.; McGivern, Niamh; Culley, Jayne; Grimes, Graeme R.; Serrels, Bryan; von Kriegsheim, Alex; et al. (Nature Communications, 2022)
In addition to central functions in cell adhesion signalling, integrin-associated proteins have wider roles at sites distal to adhesion receptors. In experimentally defined adhesomes, we noticed that there is clear enrichment of proteins that localise to the nucleus, and conversely, we now report that nuclear proteomes contain a class of adhesome components that localise to the nucleus. We here define a nucleo-adhesome, providing experimental evidence for a remarkable scale of nuclear localisation of adhesion proteins, establishing a framework for interrogating nuclear adhesion protein functions. Adding to nuclear FAK’s known roles in regulating transcription, we now show that nuclear FAK regulates expression of many adhesion-related proteins that localise to the nucleus and that nuclear FAK binds to the adhesome component and nuclear protein Hic-5. FAK and Hic-5 work together in the nucleus, co-regulating a subset of genes transcriptionally. We demonstrate the principle that there are subcomplexes of nuclear adhesion proteins that cooperate to control transcription.